Social Nesting, Animal Welfare, and Disease Monitoring - Giménez-Llort, Lydia (Animals (Basel), 2021)
SIMPLE SUMMARY: Most standardized tools to evaluate welfare and disease progression in animals assess the individuals, while social behaviors are scarcely monitored, despite being useful to detecting acute illness and chronic and mental health problems. The main reason is that social behavior is complex and time-consuming. We are currently using the nests built by animals living together, a species-typical behavior naturally occurring in standard housing conditions, to monitor them. Here, we provide an example of its use to evaluate social deficits and the long-term effects of a neonatal tactile-proprioceptive sensorial treatment from postnatal day 1 to 21, in male and female adult mice modeling Alzheimer’s disease compared to mice with normal aging. Social nesting was worse in the mutants, mostly in males, since the number of days needed to build a perfect nest was longer or unsuccessful in a three-day test. Early life intervention was successful. Social nesting, easily included in housing routines, can be a useful tool to assess animal welfare, monitor disease progress, and evaluate potential risk factors and effects of preventive/therapeutical strategies. Other advantages, such as being a noninvasive, painless, simple, short, and low-cost, rend social nesting feasible to be implemented in most animal department settings. ABSTRACT: The assessment of welfare and disease progression in animal models is critical. Most tools rely on evaluating individual subjects, whereas social behaviors, also sensitive to acute illness, chronic diseases, or mental health, are scarcely monitored because they are complex and time-consuming. We propose the evaluation of social nesting, a species-typical behavior naturally occurring in standard housing conditions, for such behavioral monitoring. We provide an example of its use to evaluate social deficits and the long-term effects of neonatal tactile-proprioceptive sensorial stimulation from postnatal day 1 to 21, in male and female adult 3xTg-AD mice for Alzheimer’s disease compared to sex- and age-matched non-transgenic (NTg) counterparts with normal aging. Social nesting was sensitive to genotype (worse in 3xTg-AD mice), sex (worse in males), profile, and treatment (distinct time to observe the maximum score and incidence of the perfect nest). Since social nesting can be easily included in housing routines, this neuroethological approach can be useful for animal welfare, monitoring the disease’s progress, and evaluating potential risk factors and effects of preventive/therapeutical strategies. Finally, the noninvasive, painless, simple, short time, and low-cost features of this home-cage monitoring are advantages that make social nesting feasible to be successfully implemented in most animal department settings.